Trading strategies in the overnight money market: Correlations and clustering on the e-MID trading platform - Daniel Fricke (Kiel Institute for the World Economy (IfW), 2012)
We analyze the correlations in patterns of trading for members of the Italian interbank trading platform e-MID. The trading strategy of a particular member institution is defined as the sequence of (intra-) daily net trading volumes within a certain semester. Based on this definition, we show that there are significant and persistent bilateral correlations between institutions' trading strategies. In most semesters we find two clusters, with positive correlations within the clusters and negative correlations between them. We show that the two clusters mostly contain continuous net buyers and net sellers of money, respectively, and that cluster memberships of individual banks are highly persistent. Additionally, we highlight some problems related to our definition of trading strategies. Our findings add further evidence on the fact that preferential lending relationships on the micro-level lead to community structure on the macro-level.
Keywords: G21; E42; 330; interbank market; socio-economic networks; community identification